Sustainable Development and Quality of Life in the City on the Example of Research in Poland and Ukraine - Kotarski, Hubert (European Journal of Sustainable Development, 2019)
The issue of sustainable development combined with the quality of life of the inhabitants is one of the key problems of modern cities. Poland and Ukraine are two closest neighbours. Rzeszow and Lviv are both university cities, which are also partner cities. The main aim of the research was to learn the opinions of students of the University of Rzeszow and the Ivan Franko University of Lviv on selected problems related to the quality of life in Rzeszow and Lviv, as well as personal and professional aspirations of students in Poland and the Ukraine. The purpose of the study was both cognitive and practical, i.e. on the one hand it focused on obtaining information on specific topics related to various aspects of the quality of life in the city and the aspirations of young people, and on the other hand it attempted at obtaining information that could be useful for both university and city authorities in the context of exploiting the significant potential of young people living in these cities. Keywords: sustainable development, quality of life, students, Poland, Ukraine